Highly Reflective Thin-Film Optimization for Full-Angle Micro-LEDs - Zhi-Ting Ye; Wen-Tsung Ho; Chia-Hui Chen (Nanoscale Research Letters, 2021)
Abstract Displays composed of micro-light-emitting diodes (micro-LEDs) are regarded as promising next-generation self-luminous screens and have advantages such as high contrast, high brightness, and high color purity. The luminescence of such a display is similar to that of a Lambertian light source. However, owing to reduction in the light source area, traditional secondary optical lenses are not suitable for adjusting the light field types of micro-LEDs and cause problems that limit the application areas. This study presents the primary optical designs of dielectric and metal films to form highly reflective thin-film coatings with low absorption on the light-emitting surfaces of micro-LEDs to optimize light distribution and achieve full-angle utilization. Based on experimental results with the prototype, that have kept low voltage variation rates, low optical losses characteristics, and obtain the full width at half maximum (FWHM) of the light distribution is enhanced to 165° and while the center intensity is reduced to 63% of the original value. Hence, a full-angle micro-LEDs with a highly reflective thin-film coating are realized in this work. Full-angle micro-LEDs offer advantages when applied to commercial advertising displays or plane light source modules that require wide viewing angles.